Diseño de herramienta para un análisis exergoeconómico en la producción de biocombustible a partir de la pulpa de café (2025)
The main objective of this project is to develop an educational tool specialized in exergoeconomic analysis. The tool will be a step-by-step guide for the application of the concepts, applicable to biomass pyrolysis processes, specifically in our case study of coffee pulp. This tool seeks to integrate the principles of exergy and economics, providing a practical tool for teaching and learning in process engineering. Exergy, which allows the evaluation of the real efficiency of systems by considering both irreversible losses and available useful energy, is complemented in this case with an economic evaluation that facilitates decision-making based on sustainability criteria and operating costs.